Construction and Selection of Two Sided Complete Chain Sampling Plans - CCHSP (0, 1) Indexed Through AOQL (International Journal of Scientific Research and Management (IJSRM), 2017)
In modern quality control practice, the professionals insist that if any defect occurs in a sample then very strict quality control measures should be adopted in order to avoid rejection. A novel algorithm for Chain Sampling Inspection called, Two sided - Complete Chain Sampling Plans CChSP(0,1) with outgoing quality limit as indexing is developed and presented in this paper. The complete Chain sampling plan gives more protection to the consumer while giving more pressure on the producer. Comparison between Ordinary Chain and Complete Chain sampling plans shows better discrimination in sentencing the good lot against the bad one. These plans provide small sample sizes by ensuring protection for the producers and at the same time assuring the consumer with the better quality level after the inspection. Tables are constructed for two sided complete chain sampling plan indexed through AOQL and illustration is also given for easy selection of the plan.